Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Semangat Kerja Pada Dinas Perhubungan Kota Bima: The Influence Of Work Environment And Work Motivation On Work Spirit In The Bima City Transportation Department - Rahmah, Sri; Mukhlis, Mukhlis; Jaenab, Jaenab (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the influence of the work environment and work motivation on work morale at the Bima City Transportation Agency. The research instrument used a Likert scale questionnaire. The study population was 189 respondents with purposive sampling obtained a sample of 34 respondents. Data collection techniques used observation, questionnaires and literature studies. Analysis with multiple linear regression. The results of the study indicate that partially the work environment has a significant effect on work morale but work motivation does not significantly affect work morale. Simultaneously, the work environment and work motivation have a significant effect on work morale at the Bima City Transportation Agency.